Arrest of ships in Germany and South Africa - a comparison - Mayerhofer, Vincent Michael (Department of Commercial Law, 2014)
The well-known German legal author H-J Puttfarken prefaces his remarks on the arrest of a vessel with the striking sentence "The arrest of a vessel is just as much a part of seafaring as distress, pirates and congested ports". Even if this comparison is doubtful since in opposition to an arrest, "distress, pirates and congested ports" are no legal institutes that are regulated by procedural rules. But the sentence shows the popularity of the maritime arrest, at least in the view of many ship owners, charters, etc. On the other hand the arrest of a vessel has now for ages often been the only possibility for debtors to realize a claim against ship owners, charterers, etc. The vessel, typically registered in some obscure legislation and cruising around in the world sea-lanes often constitutes the only valuable asset of a company, which itself is registered in some sunny island-state. This and much more makes the arrest of vessel so import for the world shipping business. This thesis aims on a comparison of two completely different legal systems one a mixture of different legal traditions and one a classical civil law jurisdiction. The thesis takes a practical approach to show differences and similarities that are relevant for the praxis. Thus the thesis does not focus a lot on the historical background, but rather shows the law and procedures how they are now. On some points which are supposed to be important, the thesis will go into details, but not on all points. Besides the two legal systems the thesis will also present some important points of the relevant international conventions since they have becomevery import in world shipping.